Molecular Basis of Human Sperm Capacitation - Puga Molina, Lis C.; Luque, Guillermina M.; Balestrini, Paula A.; Marín-Briggiler, Clara I.; Romarowski, Ana; Buffone, Mariano G. (Frontiers in Cell and Developmental Biology, 2018)
In the early 50s, Austin and Chang independently described changes that are required for sperm to fertilize oocytes in vivo. These changes were originally grouped under the name of “capacitation” and were the first steps on the path of development of in vitro fertilization (IVF) in humans. Followed these initial and fundamental findings, a remarkable number of observations led to characterize the molecular steps behind this process. The discovery of certain sperm-specific molecules and the possibility to record ion currents through patch-clamp approaches helped to integrate the initial biochemical observation with the activity of ion channels. This is of particular importance in the male gamete due to the fact that sperm are transcriptionally inactive. Thus, sperm must control all these changes that occur during their transit through the male and female reproductive tract by complex signaling cascades that include post translational modifications. This review is focused on the principal molecular mechanisms that govern human sperm capacitation with particular emphasis in comparing all the reported evidence with the mouse model.